2001
DOI: 10.1007/s10189-001-8042-8
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The phase behaviour and structure are reported of a new type of frustrated side-chain liquid crystalline (LC) polymer, a polyacrylate with phenylbenzoate mesogenic side groups and a narrow polydispersity. At a high degree of polymerisation the LC polymers show a nematic, a smectic-A d , a re-entrant nematic and aC phase, for shorter chains only a nematic and aC phase. This constitutes a new example of nematic re-entrance for which the driving field is the length of the polymer chain. The smectic-A d layers con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…It can be well fitted by the Gaussian lineshape to reproduce the experimental FWHM, (2)  0.55°, which can be related to the presence of small domains with a uniform orientation of helix axes in the EZL10/10 sample. An average linear size L of these domains can be estimated as L = 2 / FWHM   / (2) [31,32]. Taking into account the used wavelength   4.4 nm (E = 283.4 eV) and the revealed value of (2) corrected to the finite instrumental resolution ( inst (2)  0.2°) [33], the linear size of domains was estimated to be about L  500 nm.…”
Section: X-ray Resonance Scatteringmentioning
confidence: 99%
“…It can be well fitted by the Gaussian lineshape to reproduce the experimental FWHM, (2)  0.55°, which can be related to the presence of small domains with a uniform orientation of helix axes in the EZL10/10 sample. An average linear size L of these domains can be estimated as L = 2 / FWHM   / (2) [31,32]. Taking into account the used wavelength   4.4 nm (E = 283.4 eV) and the revealed value of (2) corrected to the finite instrumental resolution ( inst (2)  0.2°) [33], the linear size of domains was estimated to be about L  500 nm.…”
Section: X-ray Resonance Scatteringmentioning
confidence: 99%
“…This could indicate the presence of some domains with twodimensional ordering of mesogens, as reported earlier for polyacrylate side group liquid crystal homopolymers. 22,23 Further analysis is not attempted here, since we are not sure whether the sample is completely aligned in a monodomain, and have no clear explanation why the d 5 5.5 nm diffuse scattering is split into two arcs, whereas the d 5 2.1 nm peak is not. The observation of this phase was reproducible, and the fact that the peaks were observed to disappear on heating and re-appear on cooling suggests that this is not a monotropic phase transition.…”
Section: Liquid Crystalline Orderingmentioning
confidence: 99%
“…[15][16][17][18] Second, in the LC oligomer system, Percec et al reported a re-entrant isotropic phase in a supramolecular disc-like oligomer when the degree of polymerization was four or five. 13 Thirdly, in the LC polymers system, the phase reentrant phenomenon was found in the end-on SCLCPs, [19][20][21][22][23] polypeptide, [24][25] and MJLCPs. [26][27] From the previous phase reentrant behaviors of MJLCPs, we were aware of that the tail length greatly influenced on the phase behavior of MJLCPs.…”
Section: Introductionmentioning
confidence: 99%